A Retrospective Cohort Study: Safety and Effectiveness of Elbasvir/Grazoprevir ± Ribavirin Compared With Ombitasvir/Paritaprevir/Ritonavir/Dasabuvir ± Ribavirin in Patients With Chronic Hepatitis C Genotype 1 Infection - Hung, Hsuan-Yu; Chen, Chung-Yu; Liao, Yi-Hsiang (Frontiers in Pharmacology, 2021)
Background The direct-acting antiviral (DAA) agents are widely used to treat Hepatitis C virus (HCV) genotype (GT) 1 infection while may cause severe liver damage. The objectives of the study were evaluated the incidence of drug-induced liver injury (DILI), sustained virologic response at post-treatment week 12 (SVR12), and recurrence rate in HCV GT 1 infection. Methods This was a retrospective cohort study included patients diagnosed with HCV GT 1 infection, who had received intervention treatment elbasvir/grazoprevir (EBR/GZR) ± ribavirin (RBV) versus ombitasvir/paritaprevir/ritonavir (OBV/PTV/r) + dasabuvir ± RBV (as control group) for 12 or 24 weeks at a regional hospital in southern Taiwan between April 2016 and August 2018. The primary outcom of the study were to compare the incidence rate ratio (IRR) of DILI via Poisson regression, secondary outcome to evaluate the effectiveness of two treatment regimens expressed as a percentage. Results The study included 149 patients in the control group and 105 patients in the intervention group who 99.33% and 98.1% patients, respectively, achieved SVR12. In the control group, 1 patient experienced relapse, whereas in the intervention group, 2 patients relapsed. Furthermore, in the control group, a total of 9 patients developed DILI as determined during follow-up care. Of these patients, 3 were 55–84 years old. In the intervention group, 6 patients developed DILI. The IRR of DILI caused by EBR/GZR treatment was 2.84 times higher than that caused by OBV/PTV/r treatment regimen. Conclusions There was no significant difference between the studied DAA regimens regarding the incidence of DILI and effectiveness during the treatment. DILI occurrence during therapy did not affect the cure rate of medication. The present study results can provide reference data for drug selection among patients with HCV.